The Influence of Audit Characteristics and Company Characteristics on Audit Report Lag - Diah Kurnia Wati; Rindu Rika Gamayuni; Sudrajat (International Journal of Asian Business and Management, 2024)
This study investigates the impact of audit characteristics, including Audit Opinion, Audit Industry Specialization, and Audit Reputation, along with company characteristics such as Company Age and Financial Distress, on Audit Report Lag in non-primary consumer sector companies listed on the Indonesian Stock Exchange from 2011 to 2022. Analyzing data from 61 companies over 12 years with 732 observations, the research employs multiple linear regression analysis in EViews12. Findings reveal that collectively, audit opinion, industry specialization, audit reputation, company age, and financial distress significantly influence Audit Report Lag. Specifically, audit opinion, industry specialization, audit reputation, and financial distress exhibit a negative impact on Audit Report Lag, while company age has a positive effect. The study recommends future research to explore other sectors and include internal company variables like independent commissioners and institutional ownership for a more comprehensive analysis. The focus solely on auditor-related variables suggests avenues for broader investigations into internal company dynamic